Unlocking the Potential of Purinergic Signaling in Transplantation. Issue 10 (28th April 2016) - Zeiser, R.; Robson, S. C.; Vaikunthanathan, T.; Dworak, M.; Burnstock, G.
Abstract : Purinergic signaling has been recognized as playing an important role in inflammation, angiogenesis, malignancy, diabetes and neural transmission. Activation of signaling pathways downstream from purinergic receptors may also be implicated in transplantation and related vascular injury. Following transplantation, the proinflammatory "danger signal" adenosine triphosphate (ATP) is released from damaged cells and promotes proliferation and activation of a variety of immune cells. Targeting purinergic signaling pathways may promote immunosuppression and ameliorate inflammation. Under pathophysiological conditions, nucleotide‐scavenging ectonucleotidases CD39 and CD73 hydrolyze ATP, ultimately, to the anti‐inflammatory mediator adenosine. Adenosine suppresses proinflammatory cytokine production and is associated with improved graft survival and decreased severity of graft‐versus‐host disease. Furthermore, purinergic signaling is involved both directly and indirectly in the mechanism of action of several existing immunosuppressive drugs, such as calcineurin inhibitors and mammalian target of rapamycin inhibitors. Targeting of purinergic receptor pathways, particularly in the setting of combination therapies, could become a valuable immunosuppressive strategy in transplantation. This review focuses on the role of the purinergic signaling pathway in transplantation and immunosuppression and explores possible future applications in clinical practice. Abstract : This article discusses the role of the purinergic signaling pathway in transplantation and immunosuppression, and explores possible future applications in clinical practice.